APPLICATION OF CLOUD TECHNOLOGIES IN PEDAGOGICAL MANAGEMENT - Маріанна Василівна Швардак (Інформаційні технології і засоби навчання, 2021)
The concept “cloud technology” in the context of pedagogical management has been revealed in the article. It has been found that cloud technologies are relevant in education, are intensively integrated into general secondary education, constitute the basis for the formation of information and educational space of an educational institution, are indispensable during the COVID-19 national quarantine. Considering the cloud environment as an environment of effective pedagogical management, the principles on the basis of which cloud technologies of educational institution management are implemented have been determined. It has been revealed that the use of cloud technologies enables the head of the general secondary education institution to fully realize the main functions and directions of pedagogical management. The main modern processes in the cloud environment have been outlined (digitalization, feedback, collaboration, delegation of powers, crowdsourcing, strategic planning, educational benchmarking, joint planning, management of professional development of teachers, PR-activities of educational institutions, control, monitoring, evaluation, testing online). The powerful capabilities of Google’s cloud services in terms of management of teachers and educational institutions in general have been analyzed. Diagnosis has been carried out to determine the state and level of awareness of the possibilities of implementing effective pedagogical management through cloud services. Principals of general secondary education institutions from two regions of Ukraine were involved. The study was conducted in three stages: before COVID-19 quarantine, during the full lockdown and during the adaptive quarantine. As a result of the diagnosis, we have identified three levels of formation of information and digital competence of the principal of an educational institution in the context of the implementation of cloud technologies in pedagogical management: harmonious, functional and unproductive. It has been found that in the conditions of quarantine restrictions, educational managers accumulated their capabilities to the maximum, mastering the necessary cloud services in a short period of time, which led to a sharp increase in their level of information and digital competence.